The impact of inserting an InAs quantum dot in the middle subcell of a triple-junction Ga0.51In0.49P/GaAs/Ge solar cell - Tewodros Adaro Gatissa; Teshome Senbeta Debela; Belayneh Mesfin Ali (AIP Advances)
In this paper, we have investigated the effect of inserting an InAs quantum dot in the middle subcell of triple-junction solar cells on the power conversion efficiency. Ga0.51In0.49P/GaAs/Ge solar cell efficiency is limited by the short circuit current of GaAs (middle subcell). To overcome this current limiting problem, we insert InAs QDs in the i-region of GaAs. The optimization of the donor and acceptor doping concentration, the emitter and base thickness of the top (Ga0.51In0.49P) and bottom (Ge) subcells, and the size of the InAs QDs were carried out in order to achieve a current match among the three subcells. Current density–voltage characteristics have been simulated and discussed for triple-junction solar cells with and without InAs QD. Inserting InAs QDs increases the short circuit current of triple-junction Ga0.51In0.49P/GaAs/Ge solar cells from 14.7 to 23.8 mA/cm2 with insignificant degradation in open circuit voltage (0.16 V). Similarly, inserting InAs QDs increases the efficiency from 26.6% to 40.1%, surpassing conventional lattice-matched triple-junction cells and rivaling advanced metamorphic designs. This improvement is attributed to enhanced current matching via QD-mediated photon absorption, with minimal voltage loss.